Bachelard et l’écologie sonore ? Philosophies musicales et sonores du lieu : Hildegard Westerkamp et Chris Watson - Solomos, Makis (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Could Bachelard, a “great listener” (Marie-Pierre Lassus) of sounds, be associated with ound ecology? In order to put forward this hypothesis, this article focuses on the notions of place and dwelling. First, it works on these notions from The Poetics of Space, while calling on other authors – Edward Casey, Martin Heidegger, Augustin Berque, Gilles Deleuze and Félix Guattari. It then develops the importance of the notion of place in music and sound art by giving examples of artistic achievements in two new genres: soundscape composition, illustrated by a piece by Hildegard Westerkamp, Beneath the Forest Floor; field recording, sound composition with the example of Chris Watson’s In St Cuthbert’s Time.